Índice de qualidade e custos em função da variabilidade temporal da água de irrigação - Zamberlan, João Fernando (2011)
Water is a fundamental resource to life in Earth and has been used in multiple ways though times. However, there has been a decrease in its availability due to the increase in its consumption which implied a quantitative reduction as well as degradation in its qualitative state. Agriculture, as the major user of this resource, has been demanded and forced to adapt to the use of qualitatively inferior waters, leaving better quality waters to urban supply. The quality of water has been disregarded in most projects and irrigation activities, but the analysis and data interpretation related to its quality are hardly comprehended by users. Another relevant factor regards the charging for water consumption, its application and treatment costs. Usually, a cost control is done, but the intrinsic water cost is not computated. This present work has the objective of elaborating a methodology through economic analysis to help in the decisive process in irrigated agriculture, considering the water treatment costs based on quality, validating the methodological procedure though the qualitative diagnosis of superficial and reservoir waters with distinctive qualitative patterns. The work involved two reservoirs which belong to the Federal University of Santa Maria and are located within one soil mapping unity, São Pedro Unity, which is classified as a typical Distrofic RED ARGISOIL. The contribution basins of both reservoirs present similar sizes, but different uses. Water samples were collected during six months in 2010 and analyzed in order to quantify the following qualitative parameters: sodium, calcium, magnesium, suspended solids, total dissolved solids, total iron, pH, RAS, electrical conductivity and total hardness. Based on these values, the irrigation water quality indexes were calculated by using a multivariate analysis through the Major Components Method while the water costs and its treatment were determined by a decision-making analysis through a decision tree based on the relation cost benefit. We conclude that there was temporal variation of the water qualitative parameters in different periods of the year. Due to this variability, different indexes without information loss were determined, generating therefore a good water characterization in the reservoirs. The methodology and the decision tree objectively demonstrate the costs regarding the water and its consequence in the production costs of different cultures, allowing simulation of different scenarios. Considering the simulation in this work, the water total cost was not relevant in comparison to the production cost, but it was identified that the total water cost represents 9.3% of the market value of the commercialized sack, that is, normally the costs provided by several entities hide the water cost which is paid by the producers unawarely. This methodology allows producers to identify and better locate the costs of their activity as well as easily interpret the qualitative parameters of irrigation waters and make more accurate decisions, mainly in relation to the irrigation management, thus, improving effective management and its rentability.